The Left-Hand 2D:4D Ratio is Superior to the Right-Hand 2D:4D Ratio in Determining the Criminal Potential of Schizophrenia Patients - Emre, Elif; Yildiz, Sevler; Aydin, Suna; Simsek, Duzgun (Imr Press, 2025)
Background:No research has yet examined the potential association between criminal activity, schizophrenia, and the second-to-fourth digit ratio (2D:4D). Therefore, the present study aimed to evaluate if the 2D:4D differs between patients with schizophrenia with and without criminal activities. Methods:There were 143 male participants in the study: 50 healthy controls and 93 patients with schizophrenia (51 with and 42 without a criminal history). The participants completed the Barratt Impulsiveness Scale (BIS), the Buss-Perry Aggression Questionnaire (BPAQ), and sociodemographic forms. A digital caliper was used to measure finger lengths in order to compute 2D:4D ratios. The Positive and Negative Syndrome Scale (PANSS) was used to measure the severity of schizophrenia. Results: BPAQ, BIS, and PANSS scores were considerably higher in schizophrenia patients with a criminal background than in those without. Schizophrenia patients with a criminal background had considerably lower right and left 2D:4D ratios than controls. Schizophrenia patients with a criminal background had a significantly lower left 2D:4D ratio than those without. In people with schizophrenia, lower 2D:4D ratios in both hands-particularly the left-are linked to criminal behavior. Conclusion: The left 2D:4D ratio in a schizophrenia patients with criminal history was a significantly lower compared with those without. Therefore, in individuals with schizophrenia, the left 2D:4D ratio may serve as an early predictor of criminal behavior. This non-invasive anatomical measurement may have the potential to help forensic investigators identify those who are more likely to commit crimes, hence improving public safety.
Keywords: crime; digit ratios; schizophrenia; 2D:4D